2021
DOI: 10.21873/anticanres.15079
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy Improves Survival After Percutaneous Biliary Drainage in Patients With Pancreatic or Biliary Tract Cancer With Biliary Obstruction

Abstract: Background: The survival benefit of chemotherapy compared to best supportive care (BSC) after percutaneous transhepatic biliary drainage (PTBD) was evaluated in patients with pancreatic or biliary tract cancer. Patients and Methods: A retrospective registry study was conducted at a tertiary-level university hospital. The endpoint was survival measured from the PTBD and the initiation of chemotherapy. Results: Among 158 patients (mean age=74 years, range=43-93 years; 51.9% women), 82 (51.9%) had pancreatic canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…In addition, poorer prognosis was independently predicted by an ASA PS 4 and ECOG PS 4. The overall median survival in our cohort was only 4.2 months after drainage, which is in agreement with previous reports (9)(10)(11)(12)(13)(14)(15)(16). In this study, the standard chemotherapy for biliary tract cancer was gemcitabine or S-1 alone.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, poorer prognosis was independently predicted by an ASA PS 4 and ECOG PS 4. The overall median survival in our cohort was only 4.2 months after drainage, which is in agreement with previous reports (9)(10)(11)(12)(13)(14)(15)(16). In this study, the standard chemotherapy for biliary tract cancer was gemcitabine or S-1 alone.…”
Section: Discussionsupporting
confidence: 93%
“…Prognosis was slightly better in patients with ASA PS3, who showed a median overall survival of 6.1 months and of whom four patient (25%) were alive at 1-year post-drainage. Prior studies have reported similar results (16).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…We calculated survival outcomes from the date of initiating nal-IRI plus 5-FU/LV treatment to avoid time bias. 24 , 25 However, time-lead bias still exists in the analysis of total survival because patients who received chemotherapy beyond second-line therapy could not have died prior to third-line therapy. The effectiveness of nal-IRI + 5-FU/LV as a third- or later-line therapy can be further clarified through comparative study deigns that include patients receiving other chemotherapy regimens or active symptom control.…”
Section: Discussionmentioning
confidence: 99%